Intestinal, Systemic, and Oral Gluten-related Alterations in Patients With Nonceliac Gluten Sensitivity. Issue 10 (November 2016) - Picarelli, Antonio; Borghini, Raffaele; Di Tola, Marco; Marino, Mariacatia; Urciuoli, Caterina; Isonne, Claudia; Puzzono, Marta; Porowska, Barbara; Rumi, Gabriele; Lonardi, Silvia; Salemme, Marianna; Tiberti, Antonio; et al.
Abstract : Background: Nonceliac gluten sensitivity (NCGS) is an emergent condition, the framework of which is yet unclear, whereas the diagnosis is suggested only by gluten-dependent symptoms after excluding wheat allergy and celiac disease (CD). Our goal was to highlight intestinal, systemic, and oral alterations to clarify the NCGS pathogenesis and identify new diagnostic tools. Study: A total of 60 NCGS patients, 20 untreated CD, 20 treated CD, and 20 healthy volunteers were recruited. The differential diagnosis among gluten-related disorders was performed by serological, allergy, and histologic tools. NCGS patients were also subjected to antigliadin antibody (AGA) detection and HLA typing. All participants underwent an oral mucosa patch test for gluten (GOMPT), whereas an oral provocation test (OPT) for gluten was performed in 26 NCGS patients. Results: About 6/60 (10%) NCGS patients showed IgG AGA-positive results, whereas 45/60 (75%) patients carried HLA-DQ2 and/or HLA-DQ8 genes. GOMPT showed positive results in 45/60 (75%) NCGS patients, 3/20 (15%) untreated CD patients, 5/20 (25%) treated CD patients, and in no healthy volunteers. No significant difference was found between the severity of symptoms reported by NCGS patients subjected to OPT with gluten-containing croissants and those who underwent OPT with gluten-free croissants. Conclusions: GOMPT seems to be a specific tool for NCGS diagnosis, although further investigations are needed to overcome limits due to the small population studied and to contextualize GOMPT false-positive results.